Pemberdayaan UMKM Melalui Legalitas Usaha di Desa Dongko Kecamatan Dongko - Windy Juli Astuti Ningtyas; Shamara Qanita; Lusia Ervi Oktaviarika; Mukhammad Ilham Aprilian; Wiwin Yulianingsih (Postgraduated Community Service Journal, 2022)
After the economic crisis in 1997-1998, the economy in Indonesia began to increase due to the existence of the Micro, Small and Medium Enterprises (MSMEs) group which had been used as a group to develop their potential to natural potential. One of them is the development of economy in Indonesia has been widely run by the people of Dongko Village through 3 (three) business groups, namely the Women's Cooperative (KOPWAN) "Kencana", Empowerment of Women Heads of Families (PEKKA), and the Women's Business Group (KUW) "Nurani Ibu" which consists of women. In trying, of course, it takes a legality to show that the business really exists. One of them is that currently the central and local governments require business owners to have a Business Identification Number or NIB. The Business Identification Number is the identity of the business actor issued by the government through the website of the OSS institution after the entrepreneur is registered. This NIB is used by business actors to obtain business licenses and / or business identities and meet the requirements for business licenses to operate. Mentoring methods implemented by writers (1) Surveys, (2) Interviews, and (3) Focused Discussions. Assistance in making NIB was carried out in Dongko Village, Dongko District, Trenggalek Regency. It is hoped that this NIB assistance can help MSMEs in Dongko Village to obtain business legality in order to facilitate the processing of other business letters, as well as show that the business does exist, operate and is worthy of standing. The target in this writing is around 20 MSMEs in Dongko Village.